PLGA nanoparticles codeliver paclitaxel and Stat3 siRNA to overcome cellular resistance in lung cancer cells - Su WP; Cheng FY; Shieh DB; Yeh CS; Su WC (International Journal of Nanomedicine, 2012)
Wen-Pin Su,1,2 Fong-Yu Cheng,3 Dar-Bin Shieh,3–6 Chen-Sheng Yeh,5–7 Wu-Chou Su1,2,81Graduate Institute of Clinical Medicine, College of Medicine, National Cheng Kung University; 2Department of Internal Medicine, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University; 3Institute of Oral Medicine, College of Medicine, National Cheng Kung University; 4Department of Stomatology, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University; 5Advanced Optoelectronic Technology Center; 6Center for Frontier Materials and Micro/Nano Science and Technology, and 7Department of Chemistry, National Cheng Kung University; 8Cancer Center, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, Taiwan.Abstract: Background: Effective cancer chemotherapy remains an important issue in cancer treatment, and signal transducer and activator of transcription-3 (Stat3) activation leads to cellular resistance of anticancer agents. Polymers are ideal vectors to carry both chemotherapeutics and small interfering ribonucleic acid (siRNA) to enhance antitumor efficacy. In this paper, poly(lactic-co-glycolic acid) (PLGA) nanoparticles loaded with paclitaxel and Stat3 siRNA were successfully synthesized, and their applications in cancer cells were investigated.Methods: Firstly, paclitaxel was enclosed by PLGA nanoparticles through solvent evaporation. They were then coated with cationic polyethylenimine polymer (PLGA-PEI-TAX), enabling it to carry Stat3 siRNA on its surface through electrostatic interactions (PLGA-PEI-TAX-S3SI). The size, zeta potential, deliver efficacy, and release profile of the PLGA nanocomplexes were characterized in vitro. The cellular uptake, intracellular nanoparticle trajectory, and subsequent cellular events were evaluated after treatment with various PLGA nanocomplexes in human lung cancer A549 cells and A549-derived paclitaxel-resistant A549/T12 cell lines with α-tubulin mutation.Results: A549 and A549/T12 cells contain constitutively activated Stat3, and silencing Stat3 by siRNA made both cancer cells more sensitive to paclitaxel. Therefore, PLGA-PEI-TAX-S3SI was synthesized to test its therapeutic role in A549 and A549/T12 cells. Transmission electron microscopy showed the size of PLGA-PEI-TAX-S3SI to be around 250 nm. PLGA-PEI nanoparticles were nontoxic. PLGA-PEI-TAX was taken up by A549 and A549/T12 cells more than free paclitaxel, and they induced more condensed microtubule bundles and had higher cytotoxicity in these cancer cells. Moreover, the yellowish fluorescence observed in the cytoplasm of the cancer cells indicates that the PLGA-PEI nanoparticles were still simultaneously delivering Oregon Green paclitaxel and cyanine-5-labeled Stat3 siRNA 3 hours after treatment. Furthermore, after the cancer cells were incubated with the synthesized PLGA nanocomplexes, PLGA-PEI-TAX-S3SI suppressed Stat3 expression and induced more cellular apoptosis in A549 and A549/T12 cells compared with PLGA-PEI-TAX.Conclusion: The PLGA-PEI-TAX-S3SI complex provides a new therapeutic strategy to control cancer cell growth.Keywords: PLGA, nanoparticle, paclitaxel, siRNA, simultaneous drug delivery